(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the agronomic performance of 17 common bean genotypes of the Carioca and Black commercial groups, between advanced lines and commercial varieties, in the Cerrado-Pantanal ecotone region. The study was developed in the experimental area of the State University of Mato Grosso do Sul, University Unit of Aquidauana, in the "dry" harvest. The experimental design used was randomized blocks, with 17 treatments and three replications. The genotypes were evaluated for the following traits: days for flowering; insertion height of the first pod; plant height; number of pods per plant; number of grains per pod; 100 grain mass; grain yield and susceptibility to diseases. The data obtained, except for the diseases, were submitted to variance analysis and the means grouped by the Scott-Knott test at 5% probability. The genotypes differed according to the variables, days for flowering, pod insertion height, 100-grain mass and yield. Under the conditions of the region, only the genotypes IAC Alvorada, IAPAR 81, TAA Bola Cheia, IAC Diplomata, BRS Esteio, Pérola, BRS Estilo, CNFC 10729 and CNFP 10 794 presented higher agronomic performance compared to the others. All genotypes were susceptible to bacterial cresting and angular staining.